2017
DOI: 10.3892/mco.2017.1307
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of metastatic refractory colorectal cancer following regorafenib failure

Abstract: Abstract. At present, there is no set strategy for the treatment of patients with colorectal cancer subsequent to the failure of standard treatment, other than the use of regorafenib (RGR) and TAS-102. The best order in which to use these drugs, and their safety and efficacy in combination with other drugs, are currently under investigation. It has been reported that RGR has a resensitizing effect on tumors that have previously failed to respond to anticancer drugs; this makes it a promising salvage therapy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In the present study, it was identified that cetuximab retreatment was as effective and tolerable therapy in patients with mCRC who had previously exhibited disease progression following an initial clinical benefit to first-line cetuximab-based therapy. A small number of previous reports have demonstrated the clinical benefit of anti-EGFR retreatment in patients with mCRC ( 9 11 ). Table V summarizes the results of 3 previous phase II studies of cetuximab retreatment in patients with mCRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, it was identified that cetuximab retreatment was as effective and tolerable therapy in patients with mCRC who had previously exhibited disease progression following an initial clinical benefit to first-line cetuximab-based therapy. A small number of previous reports have demonstrated the clinical benefit of anti-EGFR retreatment in patients with mCRC ( 9 11 ). Table V summarizes the results of 3 previous phase II studies of cetuximab retreatment in patients with mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, trifluridine/tipiracil (TAS-102) and regorafenib monotherapies have demonstrated improvement in overall survival in patients with CRC disease progression following standard therapies, and these drugs remain additional treatment options ( 7 , 8 ). However, in addition to the improvement in survival for patients with mCRC, a number of patients who exhibited good disease control following chemotherapy also exhibited good long-term performance status and remain suitable for additional therapy following progression beyond third- or fourth-line treatment ( 9 ). At present, a standard treatment for those who are resistant towards or unable to tolerate these agents does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most malignant tumors with a mortality rate of 9% among all cancer-related deaths [1] . It is also viewed as a refractory malignancy because a considerable proportion (>20%) of CRC was metastatic upon diagnosis, and nearly one-third of CRC relapsed after the surgical resection [2] . Such neoplasm usually originates from the epithelial cells lining the colon or rectum in the gastrointestinal tract [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Re-challenge chemotherapy is defined as the re-introduction of previously used chemotherapy with oxaliplatin or irinotecan-based regimens at least 9 months after the end of the initial exposure. Re-challenge chemotherapy constitutes an important option in patients who still present with good performance status and organ function reserve, especially in those in whom the initial chemotherapy was discontinued before progression of the disease (e.g., due to cumulative toxicities) [63][64][65]. Such approach did not shorten the period of the best supportive care and, more importantly, might prolong OS [65].…”
Section: Re-challenge Chemotherapymentioning
confidence: 99%
“…Re-challenge chemotherapy constitutes an important option in patients who still present with good performance status and organ function reserve, especially in those in whom the initial chemotherapy was discontinued before progression of the disease (e.g., due to cumulative toxicities) [63][64][65]. Such approach did not shorten the period of the best supportive care and, more importantly, might prolong OS [65]. According to Chambers et al, clinical benefit rate (defined as the proportion of patients with partial response or stable disease) after re-challenge chemotherapy was 75.5% and time to progression equaled 6.5 months [63].…”
Section: Re-challenge Chemotherapymentioning
confidence: 99%